The Financial Accelerator and the Real Economy: A Small Macroeconometric Model for Norway with Financial Frictions - Roger Hammersland; Cathrine Bolstad Træe (Norges Bank, 2012)
This paper studies the salient features of a core macroeconometric model that allows for self-reinforcing co-movements between credit, asset prices and real economic activity. In contrast to the economic literature that cultivates highly stylized model representations aimed at illustrating the workings and the implications of such features, the model of this paper integrates no less than two mutually reinforcing financial accelerator mechanisms in a full-fledged core macroeconomic model framework. Noteworthy, the impulse responses of such a model turns out to be very much in line with the ones one would have expected using a typical SVAR/DSGE model, though the amplitude of shocks is in most cases stronger than the ones pertaining to these kinds of models. This is due to the workings of the financial accelerators that contribute to the magnification of the effects of shocks to the economy. Furthermore, a forecast comparison undertaken between our model and an alternative macroeconometric model without a financial block, suggests that financial feedback mechanisms may improve the forecasting properties of theory-informed macroeconometric models.
hdl:11250/2507201
Keywords: E1; E32; E44; 330; the financial accelerator; structural vector error correction modelling; impulse response analysis; forecasting